2016
DOI: 10.1039/c6sm00546b
|View full text |Cite
|
Sign up to set email alerts
|

Matched elastic constants for a perfect helical planar state and a fast switching time in chiral nematic liquid crystals

Abstract: Chiral nematic liquid crystals possess a self-assembled helical structure and exhibit unique selective reflection in visible and infrared light regions. Their optical properties can be electrically tuned. The tuning involves the unwinding and restoring of the helical structure. We carried out an experimental study on the mechanism of the restoration of the helical structure. We constructed chiral nematic liquid crystals with variable elastic constants by doping bent-dimers and studied their impact on the resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This transient structure quickly transforms into another transient structure that resembles a normal cholesteric with a pitch that is larger than the equilibrium cholesteric pitch.Yu et al (M. Yu et al 2016) used CB7CB as a dopant to a cholesteric mixture and demonstrated that the decrease of the bend elastic constant in these mixtures can speed up the transition from the homeotropic to intrinsic planar cholesteric state, with a response time on the order of tens of milliseconds. Furthermore, the transient conical and planar states help to improve the quality of the resulting planar structure, avoiding defects such as dislocations and oily streaks (M Yu et al 2016…”
mentioning
confidence: 99%
“…This transient structure quickly transforms into another transient structure that resembles a normal cholesteric with a pitch that is larger than the equilibrium cholesteric pitch.Yu et al (M. Yu et al 2016) used CB7CB as a dopant to a cholesteric mixture and demonstrated that the decrease of the bend elastic constant in these mixtures can speed up the transition from the homeotropic to intrinsic planar cholesteric state, with a response time on the order of tens of milliseconds. Furthermore, the transient conical and planar states help to improve the quality of the resulting planar structure, avoiding defects such as dislocations and oily streaks (M Yu et al 2016…”
mentioning
confidence: 99%
“…A wider viewing angle in the infrared spectrum region for a graphene glass-based ChLC device (Figure i) is thus achieved compared with the above-mentioned device with a PVA-polymer alignment layer. It should be noted that the visible light reflection of ChLCs is also possible through the optimization of parameters such as viscosity, , elastic constants, and the appropriate graphene nanostructures with controlled patterns of lines or dots. …”
Section: Resultsmentioning
confidence: 99%
“…The validity of the Grandjean planar texture in the RM50-CLC sample after voltage treatment has been double-checked by the visible light transmission spectrum without any polarizer, which shows transmittance of ~80% on average compared to that of ITO glass used (data not shown). The resultant Grandjean planar texture with high transparency in visible light might be attributable to the CB7CBdoped CLC host with matched bend and twist elastic constants so that the nucleation process for the transition from the transient planar state to the initial Grandjean state was reduced [34]. Subsequently, a continuous voltage waveform comprising V = 100 V rms at 5 kHz for 3 s and V = 0 for 7 s in a period was designated to repeatedly unwind and rewind the CLC helix.…”
Section: Stability and Recoverability Of Pn-ulh Texturesmentioning
confidence: 99%